The role of the Community Development Authority in rehabilitating re-offenders in the Emirate of Dubai through post-care programs : A field study - AlBanna, Ayesha; Bayomy, Mohamed (Al-Adab Journal, 2024)
The study aimed to identify the nature of the after-care programs provided by the Community Development Authority in the Emirate of Dubai and their impact on ex-offenders from their perspective. The study adopted a descriptive methodology using a case study guide and employed the interview tool. The researcher used a non-probability sample as it was deemed most suitable for the study's topic. The sample consisted of 16 ex-offenders from Dubai Central Prison. The study reached several key findings, including: the majority of the study cases were drug-related offenses; most of the participants were married with children, and their monthly family income ranged from average to limited, with many experiencing unemployment. The post-care programs do not cover all areas and are insufficient for the interviewed cases. They lack comprehensive post-care programs, and most of the staff members are unqualified and not updated to cope with the changing variables in society. Peer influence and a lack of a sense of responsibility are among the main obstacles preventing compliance with post-care programs. Additionally, the programs do not provide employment opportunities. The researcher suggests the establishment of a committee to reassess the post-care programs and the staff working on them, as well as the addition of economic support programs. The involvement of ex-offenders in the development and implementation of these programs is also recommended.